Anorexia‐cachexia syndrome in hepatoma tumour‐bearing rats requires the area postrema but not vagal afferents and is paralleled by increased MIC‐1/GDF15. Issue 3 (26th December 2016) - Borner, Tito; Arnold, Myrtha; Ruud, Johan; Breit, Samuel N.; Langhans, Wolfgang; Lutz, Thomas A.; Blomqvist, Anders; Riediger, Thomas
Abstract: Background: The cancer‐anorexia‐cachexia syndrome (CACS) negatively affects survival and therapy success in cancer patients. Inflammatory mediators and tumour‐derived factors are thought to play an important role in the aetiology of CACS. However, the central and peripheral mechanisms contributing to CACS are insufficiently understood. The area postrema (AP) and the nucleus tractus solitarii are two important brainstem centres for the control of eating during acute sickness conditions. Recently, the tumour‐derived macrophage inhibitory cytokine‐1 (MIC‐1) emerged as a possible mediator of cancer anorexia because lesions of these brainstem areas attenuated the anorectic effect of exogenous MIC‐1 in mice. Methods: Using a rat hepatoma tumour model, we examined the roles of the AP and of vagal afferents in the mediation of CACS. Specifically, we investigated whether a lesion of the AP (APX) or subdiaphragmatic vagal deafferentation (SDA) attenuate anorexia, body weight, muscle, and fat loss. Moreover, we analysed MIC‐1 levels in this tumour model and their correlation with tumour size and the severity of the anorectic response. Results: In tumour‐bearing sham‐operated animals mean daily food intake significantly decreased. The anorectic response was paralleled by a significant loss of body weight and muscle mass. APX rats were protected against anorexia, body weight loss, and muscle atrophy after tumour induction. In contrast, subdiaphragmatic vagal deafferentation did not attenuate cancer‐induced anorexia or body weight loss. Tumour‐bearing rats had substantially increased MIC‐1 levels, which positively correlated with tumour size and cancer progression and negatively correlated with food intake. Conclusions: These findings demonstrate the importance of the AP in the mediation of cancer‐dependent anorexia and body weight loss and support a pathological role of MIC‐1 as a tumour‐derived factor mediating CACS, possibly via an AP‐dependent action.